Experimental progress of 209Bi(n,G)210gBi cross-section measurement based on polonium self-deposition technique - Feng Xu; Yushou Song; Size Chen; Jinlong wang; Guobing Yu; Deyun Wen; Dan Xiao; Yong Guo; Lei Ren (International Journal of Advanced Nuclear Reactor Design and Technology, 2025)
Lead bismuth eutectic alloy (LBE:44.5 wt%Pb+55.5 wt%Bi) is an important coolant candidate for fourth-generation reactors due to its good physical and chemical properties. However, the risk of radioactive polonium radiation protection caused by liquid lead-bismuth alloy as the main coolant of the reactor has become an important problem that must be paid attention to in the development of the lead-bismuth reactor. The 209Bi(n,γ)210gBi reaction is a key source term for 210Po generation in lead-bismuth reactors. Accurate measurement of the 209Bi(n,γ)210gBi cross section is important for assessing the risk of radioactive polonium release from lead-bismuth reactors. At present, the reaction cross section can be measured by the online method of directly measuring the cascade prompt gamma rays of the capture reaction or the offline method of measuring 210gBi decay product 210Po. To solve this problem, a210Po self-plating enrichment method based on isotope dilution α energy spectrometry with electrode movement is proposed. By optimizing the key conditions of the self-plating process, the enrichment rate of 210Po is effectively improved, which will help solve the problem of insufficient sensitivity of the direct measurement method of 209Bi(n,γ)210gBi low yield. The experimental results show that this technique is suitable for 209Bi(n,γ)210gBi post-processing measurement, and is of great significance for the study of neutron irradiation products of lead-bismuth eutectic alloys.